Survivable time-aware traffic grooming in spatial division multiplexing elastic optical networks with minimized crosstalk. (May 2020) - Hosseini, Soheil; Ghaffarpour Rahbar, Akbar; Jafari-Beyrami, Mohammad
Abstract: The space division multiplexing (SDM) technology with multi-core fiber (MCF) is a solution to increase the capacity of optical links. MCF undergoes involuntary challenges due to the interference of transmitted signals on congested multiple cores, named inter-core crosstalk (XT). On the other hand, to protect the huge traffic of users, applying survivability and traffic grooming at the same time is necessary. We study dynamic survivable time-aware grooming, routing, spectrum and core allocation considering XT in SDM-enabled elastic optical networks (SDM-EONs) with MCF and propose survivable grooming time-aware XT-unaware/aware (TXTUSG/TXTASG) algorithms. Using these algorithms, full survivability and optimum utilization of network resources are provisioned by the dedicated path protection and grooming strategies. In addition, the quality of receiving signals is assured by overcoming XT. Furthermore, an attempt is made to reduce fragmentation by involving time dimension. Our simulation results affirm that blocking rate always decreases in suggested algorithms owing to fragmentation reduction, spectrum utilization increase, and bandwidth variable transponders performance enhancement.